2009
DOI: 10.1149/1.3229978
|View full text |Cite
|
Sign up to set email alerts
|

Critical Pitting Temperature of a 22-05 Duplex Stainless Steel and Pitting Potential Statistics

Abstract: The Critical Pitting Temperature of a 22-05 type duplex stainless is investigated using both potentiodynamic and potentiostatic techniques. The potentiodynamic technique leads to a lower CPT value than the potentiostatic one. The pitting potential distribution near the CPT is determined using a multichannel device. A 10°C transition temperature interval is evidenced in which pitting probability gradually increases from 0 to 1. A conservative CPT should then be defined as the lowest boundary of this temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The scatter observed in CPT data can now be addressed. As mentioned above, the measured values of CPT and their distribution range have been found to increase with (a) decrease of exposed area, 8,9 (b) increase of alloying content or decrease of susceptible microstructural surface features, 8,10-14 and (c) decrease of applied potential (for potentiostatic CPT measurements). 8,14 According to the proposed CPT model, the increase of CPT values and their distribution in (a) and (b) are caused by the decreased susceptibility of the alloy, whereas for (c) these increases are caused by a decrease of the driving force for passive film breakdown.…”
Section: Critical Pitting Temperature Based On Pit Growth Stability-mentioning
confidence: 76%
See 1 more Smart Citation
“…The scatter observed in CPT data can now be addressed. As mentioned above, the measured values of CPT and their distribution range have been found to increase with (a) decrease of exposed area, 8,9 (b) increase of alloying content or decrease of susceptible microstructural surface features, 8,10-14 and (c) decrease of applied potential (for potentiostatic CPT measurements). 8,14 According to the proposed CPT model, the increase of CPT values and their distribution in (a) and (b) are caused by the decreased susceptibility of the alloy, whereas for (c) these increases are caused by a decrease of the driving force for passive film breakdown.…”
Section: Critical Pitting Temperature Based On Pit Growth Stability-mentioning
confidence: 76%
“…Despite the description of CPT as a deterministic transition with a narrow distribution, measured values of CPT can be statistically distributed. Results reported in the literature indicate that the distribution range of CPT values from replicated measurements increases with (a) a decrease of exposed area, 8,9 (b) an increase of alloying content or decrease of susceptible microstructural surface features, 8,[10][11][12][13][14] and (c) a decrease of applied potential (for potentiostatic CPT measurements). 8,14 In some cases, the distribution range from replicated measurements can be expanded up to 20 • C. 10,14 Interestingly, in these cases, the conditions showing expanded distribution also exhibit increases in the mean value of the CPT.…”
Section: Introductionmentioning
confidence: 99%
“…Peguet et al 29 also investigated the CPT of DSS 2205 based on a statistical analysis and found that its CPT ranged from 52 to 54°C in 0.5 M Cl − solution. Furthermore, Dussart et al 30 and Deng et al 31 claimed that the CPT value of DSS 2205 was around 60°C through potentiostatic method in 0.5 or 1 M NaCl solutions. In this case, it is believed that the DSS 2205 maintains a well-passivated condition and stays away from the pitting corrosion below 50°C.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the pitting corrosion caused by the square wave is relatively weak. As mentioned above, [28][29][30][31] many authors proposed that the CPT of DSS 2205 is greater than 50°C or even approaches 60°C in Cl − solution. However, these three waveform AV interferences all induce pitting corrosion on DSS 2205 samples when the solution temperature is 50°C.…”
Section: Etching On Dssmentioning
confidence: 99%
“…However, to our knowledge, the independence and reproducibility of potentiostatic CPT were overestimated. For instance, some studies showed that chloride concentration had a considerable influence on CPT results; potentiostatic CPT was quite discrete in highly alloyed steels and tended to give higher values than potentiodynamic CPT . In our opinion, available literature is still insufficient to clarify the discrepancy among different studies and it is necessary to reassess the reliability of CPT.…”
Section: Introductionmentioning
confidence: 96%